Karyotype analysis of five endemic Bellevalia species from Turkey - Dogan, Gulden; Kiran, Yasar; Eroglu, Huseyin; Fidan, Mehmet; Pinar, Sueleyman Mesut (Univ Tokyo Cytologia, 2024)
This study aimed to investigate the somatic chromosome numbers and morphometric properties of chromosomes in five endemic species of the genus Bellevalia Lapeyr. (Asparagaceae) from Turkey. The examined taxa are B. behcetii Pinar, Ero & gbreve;lu & Fidan, B. koyuncui Karabacak & Yildirim, B. pseudolongipes Karabacak & Yildirim, B. sasonii Fidan, and B. vuralii B.& Scedil;ahin & Aslan. Karyological techniques were employed to assess the chromosome number and morphology of the species. The genus Bellevalia is by a basic chromosome number x = 4. Chromosome numbers of the species were determined B. behcetii , B. koyuncui , B. pseudolongipes , and B. sasonii 2 n =2 x = 8, while B. vuralii 2 n =4 x = 16, was determined. Satellites were observed in two species; B. behcetii and B. vuralii . Using the Stebbins classification system, species were categorized as class 3A. Additionally, various parameters such as chromosome number, total chromosome length, relative length, arm ratio, centromere index, and centromere states, karyotype asymmetry values, and karyotype formula were determined. Notably, this study marks the first time that chromosome numbers of B. sasonii have been defined, contributing valuable new data to the systematics of these species.
Keywords: Asparagaceae; Bellevalia; Chromosome number; Karyotype; Turkey